FACT SHEET: CAMPAIGN FOR SMOKE-FREE SKIES WORLDWIDE (Tufts Archival Research Center, 2007)
Press release detailing the goals of the Campaign for Smoke-Free Skies Worldwide. States the long-term objective of a total prohibition on smoking on all flights. Argues that domestic bans are already successful in varying locations and that a worldwide ban is needed for health and safety reasons. Provides reassurance that many smokers also agree with the need for this restriction.